Agreement On Settling The Flight Informtion Region (FIR) Boundary Line Between Indonesia And Singapore On Indonesia's Southernmost Island - Lenny Husna; Ukas Ukas (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
The goal of this research is to determine how the legal position of Singapore returning Flight Information Region (FIR) over the Riau Islands is founded on international law, which is the basis for delegating authority to Singapore to manage FIR over the Riau Islands. International legal recognition of sovereignty in airspace is contained in Article 1 of the 1919 Paris Convention, which states that